Daya Simpan Bakso Dengan Level Subtitusi Tepung Umbi Gembili Sebagai Filler Ditinjau dari Kualitas Fisik : Shelf Life of Meatballs with Substitution Level of Gembili Tuber Flour as Filler Reviewed from Physical Quality - Zubair, Arif; Mudawaroch, Roisu Eny; Wibawanti, Jeki Mediantari Wahyu (Jurnal Riset Agribisnis dan Peternakan, 2025)
The process of making meatballs requires a filler material, namely tapioca flour. Tapioca flour has disadvantages such as high moisture and calorie content and low protein. Flour that is an alternative as a filler, namely gembili tuber flour, can be used because it contains inulin, higher protein, and lower moisture content. The purpose of this study is to determine the shelf life and influence of the substitution level of gembili tuber flour as a filler on the physical quality of meatballs. The study used a Complete Random Design (RAL) with 5 treatments of gembili flour substitution at the P0 to P4 level and the storage period of meatballs for 0, 5, 10, and 15 days. The results of the physical test showed that the substitution treatment of the level of gembili flour had a real effect on the water content and pH value (P < 0.05), but did not have a real effect on the shrinkage of the cooking of meatballs. The shelf life of meatballs has a real effect on the pH value and ripening shrinkage (P < 0.05), but it does not have a real effect on the moisture content of meatballs. There was an interaction between the treatment of the substitution level of gembili flour and the shelf life to affect the pH value of meatballs (P < 0.05), but there was no interaction between the value of moisture content and the shrinkage of meatballs. The conclusion of this study physical test showed that the substitution level of gembili flour had a real effect on the water content, pH, but did not have a real effect on the shrinkage of meatball ripening. How long to store influential meatballs noticeable on the pH value and shrinkage of meatballs, but no real effect on the moisture content of meatballs. There was an interaction between the substitution levels of gembili flour and how long to store meatballs on the pH value of meatballs but there is no interaction between the value of moisture content and the depletion of meatballs.